“Marcação ou partitura?” particularidades conceituais no trabalho de tradução dentro do GITA - Barbosa Júnior, Augusto Jones de Aragão (2024)
This work aims to make a memorial report about my personal trajectory as a research member of the Research Group on Psychophysical Training of Actors (GITA), belonging to the Degree in Theater course at UFPA. Aiming to report how I joined the course and the research group, in addition to contact with the theoretical and practical area that surrounds it, such as training, dramatization and the psychophysical understanding of my body.